Estudo fitoquímico e farmacológico de Lippia thymoides Mart. & Schauer (Verbenaceae) - Silva, Fabrício Souza (2012)
The species Lippia thymoides (Verbenaceae), popularly known as “alecrim do mato” or “alecrim do campo”, is used in the folk medicine to treat wounds, bronchitis, rheumatism and fever. In this work was investigated the phytochemical and pharmacological profile oh this species, correlating with its popular use. Essential oils obtained in the four seasons had as majoritary constituent the sesquiterpene -caryophyllene. The species L. thymoides presented potent antioxidant activity in the DPPH assay, probably due to elevated content of phenolics. Essential oils inhibited the growth of bacteria Staphylococcus aureus, while the dichlorometane and ethyl acetate fractions from leaves and stems methanolic extracts inhibited the growth of S. aureus, Micrococcus luteus and Bacillus cereus. Methanolic extracts from leaves and stems not stimulated the cutaneous wound healing in rats. Methanolic extract from leaves significantly reduced the rectal temperature in rats submitted to hyperthermia induced by hyperpyrexia with injection of the Saccharomyces cerevisiae. Essential oil these specie presented antinociceptive activity in mices, probably due to anti-inflammatory effect of b-caryophyllene, 1,8-cineole, camphene and borneol. The specie L. thymoides presented spasmolytic activity in vitro in isolated organs, with the essential oils relaxing rat uterus and rat aorta of endothelium-independent manner and methanolic extracts and fractions from leaves and stems relaxing guinea-pig trachea smooth muscles. This last effect might be related to competitive antagonism with muscarinic receptors, as it was observed with the dichloromethane fraction from methanolic extract of the leaves. These results showed that L. thymoides is a source of substances of pharmaceutical interest, explaining partially the folk use of this species to treat wounds, rheumatism, fever and bronchitis.